2022
DOI: 10.1002/iid3.662
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 inhibits neutrophil phagocytosis through the EP2R–cAMP–PTEN pathway

Abstract: Prostaglandin E2 (PGE2) is a potent lipid mediator of inflammation that modulates immune cell function by binding to unique G protein‐coupled receptors (EP receptors). PGE2 production increases during microbial infection and inflammation. In this study, we assessed the effect of PGE2 on the phagocytosis of bacteria by neutrophils, which are key players during infection and inflammation. We also looked for specific EP receptor signaling pathways that contributed to the neutrophil phagocytic activity. PGE2 (50–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Given that meloxicam treatment also inhibited phagocytosis by neutrophils and macrophages, the resulting slower clearance of pathogens would automatically prolong the inflammation. PGD 2 enhances the phagocytic activity of neutrophils and macrophages (Pereira et al, 2015(Pereira et al, , 2018, whereas PGE 2 is an inhibitor (Aronoff et al, 2004;Wang et al, 2022). Because phagocytic activity depends on the cell's interpretation of the sum of incoming positive and negative signals, the final regulation of phagocytosis by neutrophils and macrophages is likely to depend on additional input from other receptors and signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that meloxicam treatment also inhibited phagocytosis by neutrophils and macrophages, the resulting slower clearance of pathogens would automatically prolong the inflammation. PGD 2 enhances the phagocytic activity of neutrophils and macrophages (Pereira et al, 2015(Pereira et al, , 2018, whereas PGE 2 is an inhibitor (Aronoff et al, 2004;Wang et al, 2022). Because phagocytic activity depends on the cell's interpretation of the sum of incoming positive and negative signals, the final regulation of phagocytosis by neutrophils and macrophages is likely to depend on additional input from other receptors and signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, PGE 2 inhibits eosinophil migration whereas PGD 2 is a chemoattractant for eosinophils (Monneret et al, 2001;Sturm et al, 2008). Similarly, PGE 2 inhibits phagocytosis by neutrophils and macrophages (Aronoff et al, 2004;Wang et al, 2022) whereas PGD 2 suppresses phagocytic activity depending on the activated receptor subtype (Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the production of PGE2 led to a reduction of phagocytosis in immune cells 24,25 . To assess the potential of Tp47 to promote PGE2 production by macrophages, cell supernatants were collected during the experiments in which macrophages were treated with different concentrations of Tp47 as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the production of PGE2 led to a reduction of phagocytosis in immune cells. 24,25 To assess the potential of Tp47 to promote PGE2 production by macrophages, cell supernatants were collected during the experiments in which macrophages were treated with different concentrations of Tp47 as described above. The results showed that the concentration of PGE2 produced by macrophages increased significantly with the increase of Tp47 concentration in a concentration-dependent manner (p < 0.001) (Figure 2a).…”
Section: Tp47 Inhibited the Phagocytosis Of Macrophages By Inducing P...mentioning
confidence: 99%